2018
DOI: 10.1017/s1041610217003076
|View full text |Cite
|
Sign up to set email alerts
|

Associations between modifiable lifestyle factors and multidimensional cognitive health among community-dwelling old adults: stratified by educational level

Abstract: Background: Cognition is multidimensional, and each domain plays a unique and crucial part in successful daily life engagement. However, less attention has been paid to multi-domain cognitive health for the elderly, and the role of lifestyle factors in each domain remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
(37 reference statements)
2
18
0
4
Order By: Relevance
“…Our empirical findings showed that maintaining good eating habits and food preferences are significantly associated with decreased dementia risk, which is consistent with some previous results 18 . Walking (more than three times per week) and watching TV (almost every day) are also practical activities that aid dementia prevention 19,20 …”
Section: Introductionsupporting
confidence: 91%
“…Our empirical findings showed that maintaining good eating habits and food preferences are significantly associated with decreased dementia risk, which is consistent with some previous results 18 . Walking (more than three times per week) and watching TV (almost every day) are also practical activities that aid dementia prevention 19,20 …”
Section: Introductionsupporting
confidence: 91%
“…Our primary analyses were robust to adjustment for multiple comparisons. Results demonstrating the importance of addressing modifiable risk factors are being reported in many countries (Perales et al, 2018;Yuan et al, 2018), and thus our findings likely have implications in other countries and populations. Nevertheless, our study cohort reflects the racial/ethnic proportions of the underlying older adult population and is largely white; replication is needed in other types of populations.…”
Section: Strengths and Limitationsmentioning
confidence: 51%
“…The RBL questionnaire was composed through existing study analysis [ 10 , 12 , 13 , 31 , 32 , 33 , 34 , 35 , 36 ]. It was designed to check the lifestyle patterns in residential life in three aspects: (1) quality of home life indicators (general frequency 1: rarely—5: always), (2) daily home activities (daily frequency 1: never—5: more than 3 h), and (3) social events at home (monthly frequency 1: less than 1–5: more than 4 times).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, it was very important to develop an RBL measurement tool that could be the basis for clustering. To this end, measurement items were constructed by analyzing studies related to the lifestyles of older people [ 10 , 12 , 13 , 31 , 32 , 33 , 34 , 35 , 36 ] ( Appendix A ). To further define the concept of residential life, existing studies on housing and residential lifestyle were also analyzed [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%